Familial adult spinal muscular atrophy associated with the VAPB gene: report of 42 cases in Brazil - Victor Kosac; Marcos R. G. de Freitas; Frederico M. Prado; Osvaldo J. M. Nascimento; Caroline Bittar (Arquivos de Neuro-Psiquiatria)
Familial spinal muscular atrophy (FSMA) associated with the vesicle-associated membrane protein-associated protein B (VAPB) gene is a rare autosomal dominant disease with late onset and slow progression. We studied 10 of 42 patients from 5 families by taking clinical histories and performing physical exams, electrophysiological studies, and genetic tests. All patients presented late onset disease with slow progression characterized by fasciculations, proximal weakness, amyotrophy, and hypoactive deep tendon reflex, except two who exhibited brisk reflex. Two patients showed tongue fasciculations and respiratory insufficiency. Electrophysiological studies revealed patterns of lower motor neuron disease, and genetic testing identified a P56S mutation of the VAPB gene. Although it is a rare motor neuron disease, FSMA with this mutation might be much more prevalent in Brazil than expected, and many cases may be undiagnosed. Genetic exams should be performed whenever it is suspected in Brazil.